1995
DOI: 10.1021/ma00108a023
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorobutyl Branch Formation and the Question of Diffusion-Controlled Propagation in the Polymerization of Vinyl Chloride

Abstract: Previously published concentrations (pbb's) of the 2,4-dichloro-n-butyl branches in poly-(vinyl chloride) (PVC) have been used to develop a simple theory that predicts pbb values as a function of monomer concentration and temperature during polymerization. The experimental values of pbb are shown to be consistent, quantitatively, with the well-known "back-biting" mechanism for dichlorobutyl branch formation. They also indicate that the activation energy for back-biting is greater than that for normal chain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 1 publication
2
23
1
Order By: Relevance
“…In recent years, we have carried out other studies that relate to defect structures. One of these led to the development of an equation that successfully predicts the BB content of PVC from the monomer concentration and the temperature during polymerization 49. The results of this study and others involving kinetic analysis45, 48 showed that the rate of chain propagation does not become controlled by diffusion in typical industrial polymerizations of VC.…”
Section: Identification and Quantification: Recent Researchmentioning
confidence: 71%
See 1 more Smart Citation
“…In recent years, we have carried out other studies that relate to defect structures. One of these led to the development of an equation that successfully predicts the BB content of PVC from the monomer concentration and the temperature during polymerization 49. The results of this study and others involving kinetic analysis45, 48 showed that the rate of chain propagation does not become controlled by diffusion in typical industrial polymerizations of VC.…”
Section: Identification and Quantification: Recent Researchmentioning
confidence: 71%
“…This approach should be successful because the activation energies for the formation of the defects ought to be greater than that for conventional chain elongation. This was found to be the case, in fact, for the back‐biting step (eq 7) that leads to structure BB, whose activation energy is higher than that for normal chain growth by some 4.4 kcal/mol 49. In recent publications, some PVC samples prepared by living radical polymerization at 25–35 °C were stated to contain no structural defects at detectable levels 55, 56…”
Section: Thermal Degradation and Stabilizationmentioning
confidence: 95%
“…In terms of tertiary chlorides, PVC chains prepared at temperatures between 40 and 828C have between 1.0 and 2,4-dichloro-n-butyl branches per 1000 monomer units. 18 It is known that the thermal stability of the PVC is a direct consequence of the structural defects concentration, which are expected to be residual in the PVC-LRP. This result is obtained by the conjunction of the following effects: low reaction temperatures; a much lower amount of growing radicals when compared with the FRP process, which are in a fast exchange with their iodine encapped dormant species.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,9,23,[25][26][27][29][30][31][32][33]42,43 The main goal of these investigations was to determine how and to what extent structural defects in PVC are formed.…”
Section: Structural Defects Contentmentioning
confidence: 99%